MIF-MediatedHemodilution Promotes Pathogenic Anemia in Experimental African Trypanosomosis - Stijlemans, Benoît; Korf, Hannelie; Sparkes, Amanda; Mazzone, Massimiliano; Odongo, Steven; Bucala, Richard; Baetselier, Patrick De (PLoS Pathogens, 2016)
Animal African trypanosomosis is a major threat to the economic development and human health in sub-Saharan Africa. Trypanosoma congolense infections represent the major constraint in livestock production, with anemia as the major pathogenic lethal feature. The mechanisms underlying anemia development are ill defined, which hampers the development of an effective therapy. Here, the contribution of the erythropoietic and erythrophagocytic potential as well as of hemodilution to the development of T. congolense-induced anemia were addressed in a mouse model of low virulence relevant for bovine trypanosomosis. We show that in infected mice, splenic extramedullary erythropoiesis could compensate for the chronic low-grade type I inflammation-induced phagocytosis of senescent red blood cells (RBCs) in spleen and liver myeloid cells, as well as for the impaired maturation of RBCs occurring in the bone marrow and spleen. Rather, anemia resulted from hemodilution. Our data also suggest that the heme catabolism subsequent to sustained erythrophagocytosis resulted in iron accumulation in tissue and hyperbilirubinemia. Moreover, hypoalbuminemia, potentially resulting from hemodilution and liver injury in infected mice, impaired the elimination of toxic circulating molecules like bilirubin. Hemodilutional thrombocytopenia also coincided with impaired coagulation. Combined, these effects could elicit multiple organ failure and uncontrolled bleeding thus reduce the survival of infected mice. MIF (macrophage migrating inhibitory factor), a potential pathogenic molecule in African trypanosomosis, was found herein to promote erythrophagocytosis, to block extramedullary erythropoiesis and RBC maturation, and to trigger hemodilution. Hence, these data prompt considering MIF as a potential target for treatment of natural bovine trypanosomosis.
Keywords: Trypanosomosis; Anemia; Pathogenic; Hemodilution